2015
DOI: 10.1007/s00348-015-1950-6
|View full text |Cite
|
Sign up to set email alerts
|

A low-cost, precise piezoelectric droplet-on-demand generator

Abstract: repeatable experiments require a reliable and precise droplet generation technique.Repeatable droplet generation is also required for a number of diverse applications ranging from inkjet printing to liquid crystal display manufacturing (Fan et al. 2008). A variety of droplet-on-demand (DOD) generators are described in the literature, but most existing designs are complex, costly, and difficult to adopt for use in other studies. Many systems are designed for the generation of droplets smaller than 500 μm in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 27 publications
0
59
0
Order By: Relevance
“…We also employed a piezoelectric droplet-on-demand generator, which produces droplets of known and repeatable size [24]. Preliminary experiments indicated that air currents can significantly alter the trajectories of the promenaders [25].…”
Section: A Setup and Methodologymentioning
confidence: 99%
“…We also employed a piezoelectric droplet-on-demand generator, which produces droplets of known and repeatable size [24]. Preliminary experiments indicated that air currents can significantly alter the trajectories of the promenaders [25].…”
Section: A Setup and Methodologymentioning
confidence: 99%
“…It consists in a home-made droplet dispenser placed above a vertically vibrated container. The dispenser is a small circular cavity sandwiched between a piezoelectric transducer and a plastic sheet with a hole of diameter 800 µm [21,22]. It is filled with silicone oil (kinematic viscosity ν = 20 mm 2 /s, surface tension σ = 20.9 mN·m −1 and density ρ = 956 kg·m −3 ) at a controlled pressure that ensures that neither can air bubbles enter the cavity, nor can the liquid leak out by itself.…”
Section: Fig 1 Experimental Setup: (A) Droplet Dispenser and (B) Vmentioning
confidence: 99%
“…We then gradually increase the forcing acceleration until the wave field generated by the pillars is formed, and track the drift of the bouncing droplets over time. For self-propelling walking droplets, where control of drop size was required, we utilize a piezoelectric droplet generator to make a single droplet of radius R = 0.395 ± 0.005 mm [31]. We then increase the forcing acceleration beyond the Faraday threshold, and direct the walking droplet towards the row of pillars.…”
Section: Trapping Of Bouncing and Walking Dropletsmentioning
confidence: 99%